2021
DOI: 10.21037/cdt-21-351
|View full text |Cite
|
Sign up to set email alerts
|

Medical treatment of pulmonary hypertension in adults with congenital heart disease: updated and extended results from the International COMPERA-CHD Registry

Abstract: Background: Pulmonary arterial hypertension (PAH) is common in congenital heart disease (CHD).Because clinical-trial data on PAH associated with CHD (PAH-CHD) remain limited, registry data on the long-term course are essential. This analysis aimed to update information from the COMPERA-CHD registry on management strategies based on real-world data.Methods: The prospective international pulmonary hypertension registry COMPERA has since 2007 enrolled more than 10,000 patients. COMPERA-CHD is a sub-registry for p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 39 publications
2
8
0
1
Order By: Relevance
“…Although only limited data were available, the use of targeted PAH medication has become widespread in PAH-CHD. The therapeutic approach has even shifted in the last decade towards more aggressive use of targeted PAH medication and combination therapy, along with recognition of the effectiveness of combination therapy ( 39 , 40 ). In one small study, initial combination therapy in PAH-CHD patients was found to improve clinical course compared with monotherapy ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although only limited data were available, the use of targeted PAH medication has become widespread in PAH-CHD. The therapeutic approach has even shifted in the last decade towards more aggressive use of targeted PAH medication and combination therapy, along with recognition of the effectiveness of combination therapy ( 39 , 40 ). In one small study, initial combination therapy in PAH-CHD patients was found to improve clinical course compared with monotherapy ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…The most extensive data on the use of PAH-specific drugs in ES patients are available for ERA, which have demonstrated a clear reduction of morbidity and mortality ( 44 ). Accordingly, in larger PAH registry studies such as COMPERA, more patients were on ERA than on PDE5 inhibitors at latest observation ( 39 ). The slight divergence in our study, in which PDE5 inhibitors remained the most common medication, may be due to the fact that some of our patients were minors and already on medication before study inclusion.…”
Section: Discussionmentioning
confidence: 99%
“…Mean ± standard deviation of the difference in values obtained by two observers in case of the measurements of end-diastolic and end-systolic TAD, TAA and TAP with a correlation coefficient between these independent values for TA dimensions during the cardiac cycle. Moreover, there is an increasing interest in the non-invasive evaluation of the right heart as recently new treatment options have become available in case of pulmonary hypertension (20). Unfortunately, only limited data are available regarding the normal values of TA dimensions assessed by non-invasive cardiovascular imaging (21)(22)(23).…”
Section: Reproducibility Of 3dste-derived Ta Measurementsmentioning
confidence: 99%
“…Medical records were reviewed for healthcare-related information, sociodemographic parameters, relevant VSD [13] Ebstein anomaly [29] d-TGA [81] d-TGA [7] PS [27] CoA [71] PA + VSD [5] Aortic aneurysm [14] TOF [69] ASD [4] MVPS [13] VSD [56] AVSD [4] IAA [1] ASD [49] ccTGA [2] ccTGA [27] Mitral valve disease [2] Connective tissue disease [23] CoA [2] AVSD [19] Ebstein anomaly [2] TA [17] PAPVC [2] PA + VSD [15] TOF [2] DIV [12] TA [2] Mitral valve disease [12] DIV [1] Cardiomyopathy, congenital [11] DORV (Fallot-Type) [1] PDA [10] DORV + TGA [1] AVSD, partial [9] AVSD, partial [1] Subaortic stenosis [9] PA + IVS [8] PAS [7] DORV (Fallot-Type) [7] TAC [6] DORV + TGA [5] HCM [4] PAPVC [4] TAPVC [4] HLHS [1] Others* [12] *…”
Section: Questionnairementioning
confidence: 99%
“…There is a gap in knowledge regarding the awareness level of patients and their primary care providers about their own disease and, the appropriate level of care needed. In addition, there is a great need for targeted medical advice (10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%